HUBUNGAN ANTARA OBESITAS SENTRAL DAN STRES DENGAN KEJADIAN HIPERTENSI PADA SOPIR - Yuldan Faturrahman; Anto Purwanto; Iseu Siti Aisyah; Rosi Santika (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
Hypertension is a cardiovascular disease. Hypertension is influenced by many risk factors such as gender, age, family history, lack of exercise, excess sodium and fat consumption, alcohol, coffee consumption, smoking, stress and obesity. This study aims to determine the relationship between obesity and stress on hypertension in bus drivers majoring in Tasik-Ciamis Cirebon. This study used a cross-sectional design with a total sample of 53 with accidental sampling technique. Statistical test results from table 4.5 based on the stress conditions of the respondents showed that the value of p = 0.010 (p 0.05), there was a relationship between central obesity and the incidence of hypertension in Microbus drivers majoring in Tasikmalaya-Ciamis-Cirebon in 2018 with a value of p = 0.035 (p 0.05). suggested to driver to care their nutrition status.